Disruption of amphetamine sensitization by alteration of dendritic thin spines in the nucleus accumbens core. Issue 3 (8th February 2022) - Cai, Wen Ting; Kim, Wha Young; Kwak, Myung Ji; Rim, Haeun; Lee, Seung Eun; Riecken, Lars Björn; Morrison, Helen; Kim, Jeong‐Hoon
Abstract: Repeated injections of psychomotor stimulants like amphetamine (AMPH) to rodents can induce behavioral sensitization, which represents a long‐lasting craving that is usually observed in human addicts. Behavioral sensitization is characteristically maintained for a long duration, accompanied by structural plasticity in some brain areas involved in reward circuitry. For example, it increased dendritic spine densities in the nucleus accumbens (NAcc), which is considered to reflect neurophysiological changes at this site, leading to addictive behaviors. The ezrin, radixin, and moesin (ERM) proteins regulate spine maturity by modifying their phosphorylation at the C‐terminal region. We previously showed that ERM phosphorylation is reduced by AMPH in the NAcc core, suggesting that ERM‐mediated spine changes at this site might be associated with AMPH sensitization. To test this hypothesis, we administered AMPH to rats according to a sensitization development schedule, with lentivirus encoding a phosphomimetic pseudo‐active mutant of radixin (Rdx T564D) in the NAcc core, and examined dendritic spines at this site. We found that compared to acute AMPH, AMPH sensitization increased thin spine density with a similar ratio of filopodia‐like to mature thin spines. However, with Rdx T564D, the density of thin spines increased, with augmented filopodia‐like thin spines, resulting in no AMPH sensitization. These results indicate that Rdx T564D forces thin spines to immaturity and thereby inhibits AMPH sensitization, for which an increase in mature thin spines is normally necessary. These findings provide significant clues to our understanding of the role of dendritic spines in mediating the development of psychomotor stimulant addiction. Abstract : The ezrin, radixin, and moesin (ERM) proteins negatively regulate spine maturity when they are active upon phosphorylation of their C‐terminal threonine residue. We examined the impact of radixin phosphorylation in the nucleus accumbens core on behavioral sensitization and dendritic spines. We found that the overexpression of a phosphomimetic pseudo‐active radixin mutant (Rdx T564D) in this site disrupted amphetamine (AMPH) sensitization. The ratio of filopodia‐like to mature thin spines was augmented by Rdx T564D, whereas it was not observed in AMPH sensitization by itself. These findings provide insights on the role of ERM proteins in the NAcc core in regulating dendritic spines and accompanied development of psychomotor stimulant addiction.